Mutations in GJB2 as Major Causes of Autosomal Recessive Non-Syndromic Hearing Loss: First Report of c.299-300delAT Mutation in Kurdish Population of Iran - Azadegan-Dehkordi, Fatemeh (J Audiol Otol, 2019)
BACKGROUND AND OBJECTIVES: Autosomal recessive non-syndromic hearing loss (ARNSHL) with genetic origin is common (1/2000 births). ARNSHL can be associated with mutations in gap junction protein beta 2 (GJB2). To this end, this cohort investigation aimed to find the contribution of GJB2 gene mutations with the genotype-phenotype correlations in 45 ARNSHL cases in the Kurdish population. SUBJECTS AND METHODS: Genomic DNA was extracted from a total of 45 ARNSHL families. The linkage analysis with 3 short tandem repeat markers linked to GJB2 was performed on 45 ARNSHL families. Only 9 of these families were linked to the DFNB1 locus. All the 45 families who took part were sequenced for confirmation linkage analysis (to perform a large project). RESULTS: A total of three different mutations were determined. Two of which [c.35delG and c.-23+1G>A (IVS1+1G>A)] were previously reported but (c.299-300delAT) mutation was novel in the Kurdish population. The homozygous pathogenic mutations of GJB2 gene was observed in nine out of the 45 families (20%), also heterozygous genotype (c.35delG/N)+(c.-23+1G>A/c.-23+1G>A) were observed in 4/45 families (8.8%). The degree of hearing loss (HL) in patients with other mutations was less severe than patients with c.35delG homozygous mutation (p<0.001). CONCLUSIONS: Our data suggest that GJB2 mutations constitute 20% of the etiology of ARNSHL in Iran; moreover, the c.35delG mutation is the most common HL cause in the Kurdish population. Therefore, these mutations should be included in the molecular testing of HL in this population.